EFFECT OF 3, 5, 3'-TRIIODOTHYRONINE (T3) HORMONE ON NUCLEIC ACID AND PROTEIN CONTENT OF THE MUSCLE AND THE GROWTH OF GIANT GOURAMY, OSPHRONEMUS GOURAMY LAC. - SRI HANDAYANI; M. ZAIRIN Jr.; ING MOK.OGINTA; MARIA BINTANG (Biotropia: The Southeast Asian Journal of Tropical Biology, 2011)
This experiment was conducted to study the effect of 3, 5, 3'-triiodothyroninc (Tj) hormone on nucleic acid and protein content of the muscle and the growth of giant gouramy, Osphronemus gouramy Lac. Five experimental diets, which contain isocaloric diets, but different in T3 hormone level were used in this experiment (0.0, 2.5, 5.0, 7.5, and 10.0 mg T3 hormone/kg diet). The experimental diets were tested to three different groups offish for sixty days feeding trial. Fish body weight in groups I, II, and III were 0.39-0.42 g/fish; 19.11 -21.99 g/fish, and 37.52-40.79 g/fish, respectively. The results showed that the highest RNA, DNA concentration and RNA/DNA ratio of the muscle were produced by 10.0 mg T3 hormone/kg diet for group I and II; and 2.5 mg T3 hormone/kg diet for group III. Similar results also were found for the protein content of the whole body, protein retention, and the daily growth rate of the fish. Key words : Osphronemus gouramy/Ti hormone/nucleic acid/protcin/growth